Expanding Horizons: From Information to Inspiration at the AAAS Annual Meeting - Stephanie Bennett; Aja Bettencourt-McCarthy; Karen Burton; Shelby Carroll; Amber Gruszeczka; Haoyong Lan; Melanie Radik (Issues in Science and Technology Librarianship)
The authors attended the 2024 annual meeting of the American Association for the Advancement of Science (AAAS) as part of a cohort of Science, Technology, Engineering, and Mathematics (STEM) librarians sponsored by the partnership between the Association of College and Research Libraries (ACRL) and AAAS. We describe two sessions, one on combating misinformation and one on open science. For these topics especially, hearing the perspectives of scientists was particularly valuable and interesting to us as librarians. We share our reasoning for attending a science disciplinary conference rather than a library conference in these days when one must carefully weigh a national or international conference against all the other demands on a librarian’s professional development budget.